2014
DOI: 10.1007/s12020-014-0351-6
|View full text |Cite
|
Sign up to set email alerts
|

Fruit intake decreases risk of incident type 2 diabetes: an updated meta-analysis

Abstract: Association between fruit intake and risk of type 2 diabetes is inconsistent. In this study, we performed a meta-analysis of all prospective cohort studies to clarify the association between fruit intake and risk of type 2 diabetes. Relevant studies were identified by searches of the PubMed and Embase databases up to November 2013. The summary relative risks of association were obtained using a fixed- or random-effects model. A total of nine prospective studies (403,259 participants, including 27,940 with inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…Several prospective studies have previously assessed the association of fruit consumption with risk of diabetes, showing inconsistent findings [6,7,9,2629]. For example, higher fruit consumption was significantly associated with diabetes incidence in the Nurses’ Health Study (with 6,358 cases) and a small Finnish study with 383 cases [6,30], with HRs of 0.82 (95% CI 0.72–0.92) and 0.69 (0.50–0.93), respectively, when comparing the highest with the lowest fruit consumption category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective studies have previously assessed the association of fruit consumption with risk of diabetes, showing inconsistent findings [6,7,9,2629]. For example, higher fruit consumption was significantly associated with diabetes incidence in the Nurses’ Health Study (with 6,358 cases) and a small Finnish study with 383 cases [6,30], with HRs of 0.82 (95% CI 0.72–0.92) and 0.69 (0.50–0.93), respectively, when comparing the highest with the lowest fruit consumption category.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the sugar content in fruit is generally higher than in vegetables, leading to concerns about its potential harmful impacts on diabetes [5]. A few prospective studies have tried to assess the effects of fruit intake on risk of diabetes, but the results have been inconsistent, with some studies showing a moderately strong inverse association [6,7] and others, including those in China [8] and in European populations [9], finding no association. Furthermore, there is very limited evidence about the effects of fruit consumption on risks of death and major vascular complications among people with established diabetes [1012].…”
Section: Introductionmentioning
confidence: 99%
“…However, no association was found between habitual pre-pregnancy fruit consumption and GDM risk in the other paper, a cohort study involving 13,475 female US nurses13. In addition, previous studies of fruit consumption and T2D risk have yielded mixed conclusions9101112. In some cases, greater fruit consumption was found to reduce T2D risk1619202122, in others, no significant association was discovered12232425.…”
Section: Discussionmentioning
confidence: 83%
“…However, some kinds of fruit also contain high levels of sugar (e.g., fructose), the excessive intake of which is likely to be harmful to human health78. Epidemiological studies have generated mixed results regarding the relationship between fruit consumption and type 2 diabetes (T2D) risk9101112. Although the Nurses’ Health Study (NHS) II investigated the association between pre-pregnancy habitual fruit consumption and GDM risk, the specific effects of fruit consumption during pregnancy have not yet been examined13.…”
mentioning
confidence: 99%
“…Furthermore, only small differences were found in dietary behavior in comparison with cohort members without diabetes [21,22]. Another study found nonlinear association of fruit intake with type 2 diabetes [23]. Muraki et al concluded that there was heterogeneity in the associations between individual fruit consumption and risk of type 2 diabetes [24].…”
Section: Introductionmentioning
confidence: 99%